2019
DOI: 10.1038/s41563-019-0388-2
|View full text |Cite
|
Sign up to set email alerts
|

Mixed proton and electron conducting double perovskite anodes for stable and efficient tubular proton ceramic electrolysers

Abstract: Hydrogen production from water electrolysis is a key enabling energy storage technology for large scale deployment of intermittent renewable energy sources. Proton Ceramic Electrolysers (PCEs) can produce dry pressurized hydrogen directly from steam, avoiding major parts of cost-driving downstream separation and compression. The development of PCEs has however suffered from limited electrical efficiency due to electronic leakage and poor electrode kinetics. Here, we present the first fully-operational BaZrO3-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
176
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(199 citation statements)
references
References 39 publications
5
176
1
5
Order By: Relevance
“…The high effectiveness of PCECs is necessary to convert a high fraction of electrons and water into hydrogen. The Faradaic efficiencies of electrolzyers based on proton conducting electrolytes have been recently reported by several research groups [52][53][54] . Electronic leakage within the electrolyte under direct current voltage becomes severe with increasing temperature and oxygen partial pressure, which can reduce the efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high effectiveness of PCECs is necessary to convert a high fraction of electrons and water into hydrogen. The Faradaic efficiencies of electrolzyers based on proton conducting electrolytes have been recently reported by several research groups [52][53][54] . Electronic leakage within the electrolyte under direct current voltage becomes severe with increasing temperature and oxygen partial pressure, which can reduce the efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…While the water splitting and oxygen reduction occur at the entire electrode surface, the improvement of mass transport is needed to make gas diffusion throughout electrode grains more necessary. The incorporation of the three-dimensional mesh-like PNC Kim et aI., 2016 38 Wang et aI., 2015 39 Chen et aI., 2015 40 Laguna-Bercero et aI., 2016 45 Ishihara et aI., 2016 46 Yang et aI., 2015 47 Peng et aI., 2010 41 Traversa et aI., 2015 42 Xie et aI., 2016 48 He et aI., 2017 49 Ding et aI., 2018 43 Kim et aI., 2018 44 Peng et aI., 2018 50 Liu et aI., 2018 51 Norby et aI., 2019 52 Haile et aI., 2019 53 electrode can make full use of the high porosity and active nanoparticles of nanofibers for superior performance. Our recent result has demonstrated that hydrogen production rate has been greatly improved by this self-architectured ultra porous layered perovskite PBSCF steam electrode 43 , e.g., 0.85 A cm −2 at 1.3 V and 600°C which was increased from regular electrode (0.55 A cm −2 ).…”
Section: Discussionmentioning
confidence: 99%
“…where G vib are the respective vibrational free energies at temperature T, see eqn (2). The total Gibbs free energy of formation of BZO (D f G BaZrO 3 ), BaO (D f G BaO ), and ZrO 2 (D f G ZrO 2 ), is then determined by the sum of the corresponding quantities in eqn (3)- (8). The temperature dependence of the (total) Gibbs free energy of formation is presented in Fig.…”
Section: Gibbs Free Energy Of Formation Of Bzo Bao and Zromentioning
confidence: 99%
“…[1][2][3] BZO is a candidate material for various applications such as solid oxide fuel cells, gas sensors, and hydrogen pumps. [4][5][6][7][8] It shows good chemical and thermodynamic stability even at very high temperature. 9,10 BZO becomes proton conducting aer exposure to humid conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation